2016
DOI: 10.1161/hypertensionaha.116.07495
|View full text |Cite
|
Sign up to set email alerts
|

Invasively Measured Aortic Systolic Blood Pressure and Office Systolic Blood Pressure in Cardiovascular Risk Assessment

Abstract: 768S troke and myocardial infarction (MI) remain common diseases with massive consequences for patients and healthcare systems.1,2 Improved risk stratification is crucial to optimize patient care and requires development of more sensitive tools to identify high-risk patients. Because blood pressure (BP) in the brachial artery differs from the BP in the aorta, to which the heart and brain are exposed, cardiovascular risk assessment based on aortic BP could potentially be superior to assessment based on office B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…We have previously demonstrated that invasively measured systolic BP and PP did not add predictive information beyond cuff systolic BP and cuff PP in mortality prediction. 30 , 31 However, the current data suggest that the interaction terms and quadratic terms in the ePWV may reflect information from the invasive BP not captured by cuff BP. These findings warrant further investigations in future studies.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We have previously demonstrated that invasively measured systolic BP and PP did not add predictive information beyond cuff systolic BP and cuff PP in mortality prediction. 30 , 31 However, the current data suggest that the interaction terms and quadratic terms in the ePWV may reflect information from the invasive BP not captured by cuff BP. These findings warrant further investigations in future studies.…”
Section: Discussionmentioning
confidence: 63%
“…The association between ePWV and stroke became significant with adjustment for invasive systolic BP or PP instead of cuff BP, which is in line with our previous studies where no added prediction from invasive systolic BP was observed, and cuff PP, but not invasively measured PP, remained significantly associated with stroke in multivariate analyses. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“… 7 The comparisons involving 4574 subjects from 5 studies revealed that central pulse pressure was associated with a marginally but non‐significantly higher relative ratio of clinical outcome than brachial pulse pressure (1.318 versus 1.188, P = .057), whereas the risk estimates for central and brachial systolic BPs were similar (1.236 versus 1.204, P = .62). 7 Subsequent comparison studies 15 , 16 , 17 , 18 reported negative results by including both central and brachial BP variables in a single model, which might complicate the interpretation due to collinearity. In the Framingham Heart Study involving around 2200 participants followed up for a median of 7.8 years, central pulsatile pressures, either calibrated from carotid pressure waveforms 15 or derived using radial artery tonometry and a generalized transfer function, 16 were not related to cardiovascular events after adjustment for common risk factors including brachial systolic BP.…”
Section: Central Versus Brachial Bp As a Risk Factormentioning
confidence: 99%
“…Central or aortic BP, however, is expected to better reflect the hemodynamic load on target organs. Indeed, clinical studies suggest that central BP shows a closer relationship with target organ damage than does brachial BP [1-3]. Preclinical heart damage assessed by left ventricular mass and large artery damage assessed by intima media thickness and pulse wave velocity (PWV) appear to be closely associated with central systolic BP (SBP) and central pulse pressure (PP).…”
Section: Introductionmentioning
confidence: 99%